ABOUT ONE OF THE UNIQUE SOURCES ON THE HISTORY OF THE UZBEK LANGUAGE IN THE XVI CENTURY - S. Gafurova (Scholar Express Journal, 2021)
The article highlights the role and description of the work "Tavorikhi Guzid - Nusratnoma" in the history of the Uzbek language, provides information about the author of the work, his copies, the date of writing. There are also some ideas about the creation of the source, its significance in the study of the history of the Uzbek language.
Keywords: Historical work; source; history; Basmala